2009
DOI: 10.1248/cpb.57.668
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Bisnor- and Norditerpene Dilactones Having 7.ALPHA.,8.ALPHA.-Epoxy-9,11-enolide Substructure from Podocarpus macrophyllus D. DON

Abstract: Podocarpus macrophyllus D. DON (Podocarpaceae) (Japanese name: Inumaki) is a dioecious evergreen tree distributed in the subtropical areas of south eastern China, Taiwan, and Japan. From this plant, flavonoids, bisflavonoids, norditerpenoids, and ecdysons have been obtained. [1][2][3][4] In our recent study, several bisnor-and norditerpenoids having potent cytotoxic activities against P388 murine leukemia cells were isolated and their structures were determined. [5][6][7] In the present study, from the root an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The known norditerpenes were identified as nagilactone F ( 4 ), inumakilactone B ( 5 ) and inumakilactone ( 6 ) 6,14–16. The 13 C NMR data of compound 6 has not been previously published and thus is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The known norditerpenes were identified as nagilactone F ( 4 ), inumakilactone B ( 5 ) and inumakilactone ( 6 ) 6,14–16. The 13 C NMR data of compound 6 has not been previously published and thus is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[1] For instance, taxol, harringtonin, and camptothecin were identified from the Taxus, [2] Cephalotaxus, [3] and Camptotheca [4] species, respectively. Previously, a variety of flavonoids, [7] biflavonoids, diterpenoids (including norditerpenoid dilactones), [8] [9] and triterpenoids [10] have been reported from Podocarpus species. [5] There are thirteen species and three variants of Podocarpus in China.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to compounds 1 and 2 , two known B-type podolactones, inumakilactone A ( 3 ) [8] and makilactone E ( 4 ) [19], along with three known totarane-type diterpenes, inumakiols D ( 5 ) and E ( 6 ), and 4 β -carboxy-19-nor-totarol ( 7 ) [8] were isolated and identified during the present study.…”
Section: Resultsmentioning
confidence: 98%
“…for C 19 H 24 NaO 6 + , 371.1465). Preliminary interpretation of its 1D and 2D NMR spectroscopic data led to the assignment of its corresponding planar structure as a B-type podolactone [10, 19]. A subsequent literature search for this chemical structure revealed that the collected 1 H and 13 C NMR data for 1 matched with those of 3-deoxy-2 α -hydroxynagilactone E ( 8 ), previously isolated from Podocarpus nagi [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation